Communication as a Tool for Exhibiting Prosocial Behavior in Dogs - Carolina Generoso; Briseida Resende; Natalia Albuquerque; Michaella P. Andrade; Carine Savalli (Animals)
Studies suggest that dogs exhibit prosocial behaviors toward humans and can rescue their guardians trapped in a box. We investigated whether dogs could communicate with an experimenter to gain access to a crying actor (the crying condition) who was visible but inaccessible, as she remained behind a fence throughout the test, or when she was simply speaking (the neutral condition). This experimenter was positioned to allow access to the actor, and the dog was free to move within the environment. Our findings indicate that dogs alternated their gazes more frequently between the actor and the experimenter, as well as between the actor and the dog’s guardian when the inaccessible actor was crying. Furthermore, the number of gazes at the guardian and the actor, as well as the duration of gazing at the actor, were greater in the crying condition. Dogs also remained closer to the actor during the crying condition. Our results suggest the dog made more communicative signals in the crying condition, bringing to light the possibility that this communication was being used as a tool to exhibit prosocial behaviors toward the actor.